The Effect of 21st-Century Learning on Higher-Order Thinking Skills (HOTS) and Numerical Literacy of Science Students in Indonesia based on Gender - Sepriyanti, N.; Nelwati, S.; Kustati, M.; Afriadi, J. (Jurnal Pendidikan IPA Indonesia, 2022)
This study discusses the importance of 21st-Century learning to improve students’ higher-order thinking skills and numerical literacy based on gender. This research is descriptive quantitative, and correlational. The subjects of this study were education and science students from nine public Islamic universities in Indonesia who were selected by purposive sampling and took statistics courses in the odd semester of 2021/2022 in terms of gender. The sample size is 213 students, with 87 males and 126 female students. Data collection method used questionnaires, observation sheets, and HOTS and numerical literacy tests. The results show that the 21st-century competency-based learning process to improve HOTS and numerical literacy of Public Islamic university students in Indonesia was in the very good category (81.67%). Students’ responses to the learning process were in the very good category (81.78%). Male students’ HOTS were higher than female students, and male students’ numerical literacy skills were lower than female students. In summary, these results suggest that gender partially influences and relates to HOTS and numerical literacy of students at nine public Islamic universities in Indonesia with a low correlation.